Dermatosis Neglecta and Chilblain Lupus Erythematosus Occurred Post Surgery of Basal Cell Carcinoma: A Case Report - Gao G; Liu J; Sun R; Liu X; Meng D; Ma W (Clinical, Cosmetic and Investigational Dermatology)
Guomin Gao,1 Jiayun Liu,1 Rui Sun,1 Xuankai Liu,1 Dan Meng,2 Weiyuan Ma1 1Department of Dermatology, Affiliated Hospital of Shandong Second Medical University, School of Clinical Medicine, Shandong Second Medical University, Weifang, Shandong, People’s Republic of China; 2Department of Dermatology, Heze Municipal Hospital, Heze, Shandong, People’s Republic of ChinaCorrespondence: Dan Meng; Weiyuan Ma, Email 1056348654@qq.com; fymaweiyuan@sdsmu.edu.cnAbstract: Dermatosis neglecta (DN) is a rare condition, often linked to psychosomatic disorders, with an unclear etiology. Chilblain lupus erythematosus (CHLE) constitutes a rare variant of cutaneous lupus erythematosus, frequently mistaken for idiopathic chilblain due to its chilblain-like lesions. To date, no instances of concurrent DN and CHLE occurring at the site of a skin flap or graft have been documented. Herein, we present a case that the occurrence of DN and CHLE developed on a skin flap at once. The simultaneous occurrence of DN and CHLE on a skin flap is exceptionally rare. Clinicians must exercise heightened vigilance due to the common misdiagnosis of CHLE. Various skin disorders can manifest on skin flaps and grafts post-transplantation. Thus, clinicians must remain vigilant for both recurrence and metastasis during post-operative monitoring, while also attending to patients’ mental well-being and the condition of skin flaps.Keywords: dermatosis neglecta, skin flap, basal cell carcinoma, chilblain lupus erythematosus